Translation and cross-cultural adaptation of the Work Rehabilitation Questionnaire (WORQ) into Danish - Thygesen, Katrine Baltzer; Korshøj, Mette; Verpe, Ida Skovgaard; Vestergaard, Lise; Escorpizo, Reuben; Mortensen, Ole Steen (Frontiers in Rehabilitation Sciences, 2023)
Purpose This study aimed to translate and cross-cultural adapt the WORQ into Danish, to examine internal consistency and test-retest reliability of the WORQ-Danish, and secondary, to test the feasibility of WORQ in the Danish context of vocational rehabilitation. Methods The translation was performed in a dual-panel approach. The panel consisted of a bilingual physician, a university student in psychology, a layperson, a specialist in social work and rehabilitation and a professor in social medicine. The ICF codes were cross-evaluated level of agreement of ICF codes for each specific WORQ item in the Danish and English version. The content validity was evaluated by the clinical physicians at an outpatient clinic in social medicine and case managers at a municipality job center. Data for the examination of internal consistency and test-retest reliability was collected at the Holbæk municipality from citizens in the working age. Test-retest took place 14 days apart. Internal consistency and test-retest reliability was tested conducting Cronbach’s alpha, intraclass correlation (ICC) and Spearman correlation analyses. Results The panel experienced only minor challenges in the translation process, leading to minor modifications. The cross-evaluation of coding in the Danish WORQ compared to the initial English version only found small deviations, while the remaining coding agreed between the initial English and the Danish items. The panel argued to add sub-codes to culturally adapt to the transportation forms generally used in Denmark. The general perception among the participating patients, citizens at the job center as well as clinical physicians and case managers were that the WORQ were easy understandable and meaningful. Conclusions This study showed that the Danish WORQ have a high content validity and usability. Nonetheless, the Danish WORQ needs to be validated against well acknowledged tools for assessing functional ability specific to work and in general.